Perinatal factors associated with amplitude‐integrated electroencephalography abnormalities in preterm infants on the first day of life - Junia Sampel de Castro; Ana Teresa Figueiredo Stochero Leslie; Ruth Guinsburg (Brazilian Society of Pediatrics, 2020)
Objective: Evaluate the association between perinatal factors and amplitude‐integrated electroencephalogram abnormalities in preterm infants on the first day of life. Methods: This was a cross‐sectional study of 60 infants with gestational age between 23 and 32 weeks, without malformations. Infants were continuously monitored by amplitude‐integrated electroencephalogram on the first day of life, for at least 3 h. The tracings were recorded and analyzed in each column for the following: burst‐suppression pattern, sleep‐wake cycle, and amplitude of the lower margin (<3 μV or <5 μV). The association of maternal complications, mode of delivery, birth weight, gestational age, neonatal sex, resuscitation procedures, hypothermia on admission, and the Score for Neonatal Acute Physiology, Perinatal Extension, Version II [SNAPPE‐II]) with amplitude‐integrated electroencephalogram alterations was assessed by multiple logistic regression. Results: A discontinuous pattern occurred in 65% of infants, and a continuous pattern occurred in 23%. The burst‐suppression pattern was associated with vaginal delivery (OR: 7.6; 95% CI: 1.1-53.1) and SNAPPE‐II ≥ 40 (OR: 13.1; 95% CI: 1.8-95.1). A lower margin of the amplitude‐integrated electroencephalogram of <3 μV was also associated with SNAPPE‐II ≥ 40 (OR: 10.6, 95% CI: 2.3-49.2), while a value <5 μV was associated with lower GA (OR: 0.51, 95% CI: 0.34-0.76). There were no associations between the perinatal variables and the absence of a sleep‐wake cycle in amplitude‐integrated electroencephalogram recordings on the first day of life. Conclusion: Biological variables and clinical severity are associated with electroencephalographic characteristics of preterm infants on the first day of life and should be considered in clinical practice when amplitude‐integrated electroencephalogram is performed. Resumo: Objetivo: Avaliar a associação entre fatores perinatais e anormalidades no eletroencefalograma de amplitude integrada em recém‐nascidos prematuros no primeiro dia de vida. Métodos: Este é um estudo transversal de 60 bebês com idade gestacional entre 23-32 semanas, sem malformações. Os recém-nascidos foram continuamente monitorados por eletroencefalograma de amplitude integrada no primeiro dia de vida por pelo menos 3 horas. Os traçados foram registrados e analisados em cada coluna para: padrão de surto-supressão, ciclo de sono-vigília e amplitude da margem inferior (< 3 μV ou < 5 μV). A associação de complicações maternas, tipo de parto, peso ao nascer, idade gestacional, sexo do neonato, procedimentos de reanimação, hipotermia na admissão e Escore para Fisiologia Neonatal Aguda, Extensão Perinatal, versão II (SNAPPE-II) com alterações no eletroencefalograma de amplitude integrada foi avaliada por regressão logística múltipla. Resultados: Um padrão descontínuo ocorreu em 65% dos recém‐nascidos e o padrão contínuo ocorreu em 23%. O padrão de surto‐supressão foi associado ao parto vaginal (OR 7,6; IC95% 1,1‐53,1) e SNAPPE‐II ≥ 40 (OR 13,1; IC95% 1,8‐95,1). Uma margem inferior do eletroencefalograma de amplitude integrada < 3 μV também foi associada com escore SNAPPE‐II ≥ 40 (OR 10,6, IC95% 2,3‐49,2), enquanto um valor <5 μV foi associado com menor IG (OR 0,51, IC 95% 0,34‐0,76). Não houve associações entre as variáveis perinatais e a ausência de ciclo sono‐vigília nas gravações de eletroencefalograma de amplitude integrada no primeiro dia de vida. Conclusão: As variáveis biológicas e a gravidade clínica estão associadas às características eletroencefalográficas dos recém‐nascidos prematuros no primeiro dia de vida e devem ser consideradas na prática clínica quando o eletroencefalograma de amplitude integrada é realizado.